2020
DOI: 10.1016/j.celrep.2020.107694
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape of Murine Long Non-Coding RNAs Reveals the Leading Transcriptome Alterations in Adipose Tissue during Aging

Abstract: SUMMARY Aging is an inevitable process that involves profound physiological changes. Long non-coding RNAs (lncRNAs) are emerging as important regulators in various biological processes but are not systemically studied in aging. To provide an organism-wide lncRNA landscape during aging, we conduct comprehensive RNA sequencing (RNA-seq) analyses across the mouse lifespan. Of the 1,675 aging-regulated lncRNAs (AR-lncRNAs) identified, the majority are connected to inflammation-related biological pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 58 publications
2
14
1
Order By: Relevance
“…This affects all tissues and can modify disease processes. For instance, during aging, certain lncRNAs are generated in white AT which are linked to inflammatory pathways implicating AT and obesity with age-related degenerative changes ( 72 ). In another example, pyroptosis, a process involving activation of the inflammasome, is controlled by the lncRNA NEAT1 in diabetic nephropathy through the action of the mir34c/NLRP3 axis ( 73 ).…”
Section: Insulin Resistance Inflammation and Diabetesmentioning
confidence: 99%
“…This affects all tissues and can modify disease processes. For instance, during aging, certain lncRNAs are generated in white AT which are linked to inflammatory pathways implicating AT and obesity with age-related degenerative changes ( 72 ). In another example, pyroptosis, a process involving activation of the inflammasome, is controlled by the lncRNA NEAT1 in diabetic nephropathy through the action of the mir34c/NLRP3 axis ( 73 ).…”
Section: Insulin Resistance Inflammation and Diabetesmentioning
confidence: 99%
“…Two main factors likely lead to the in vivo heterogeneity of senescent cells. First, during the RNA-sequencing analysis of gene expression changes in various mouse organs, most aging-related changes were grouped by organ (Zhou et al, 2020). However, the different organs have varying epigenetic programs and microenvironments and undergo diverging aging processes (Ashapkin et al, 2017).…”
Section: In Vivo Transcriptomic Study Of Senescent Cellmentioning
confidence: 99%
“…snRNA-seq intrinsically enriches for nuclear localized transcripts, and previous studies have reported enrichment of lncRNAs in snRNA-seq libraries over scRNA-seq (Grindberg et al 2013;Zeng et al 2016). We hypothesized that nuclear enrichment of lncRNAs could be advantageous for characterizing adipose tissue because multiple lncRNAs have also been implicated in regulating adipogenesis (Sun et al 2013;Ding et al 2018;Wei et al 2016;Sun and Lin 2019;Zhou et al 2020). We tested this hypothesis in our in vitro system by profiling adipogenic regulatory lncRNAs in our whole-cell and nuclear libraries derived from white preadipocytes, after normalization.…”
Section: Gene Length-associated Detection Bias In Single-nuclei Rna-smentioning
confidence: 97%